2017
DOI: 10.1371/journal.pone.0172167
|View full text |Cite
|
Sign up to set email alerts
|

Career interest and perceptions of nephrology: A repeated cross-sectional survey of internal medicine residents

Abstract: BackgroundInterest in nephrology careers among internal medicine residents in the United States is declining. Our objective was to assess the impact of the presence of a nephrology fellowship training program on perceptions and career interest in nephrology among internal medicine residents. A secondary objective was to identify commonly endorsed negative perceptions of nephrology among internal medicine residents.MethodsThis was a repeated cross-sectional survey of internal medicine residents before (Group 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…Although this study's results showed adequate current nephrology trainee densities in high-income countries, many studies have shown decreased interest in the field. 14,27 Some high-income countries rely on foreign-trained doctors to cover shortages in nephrology manpower. For example, a study from Oman showed that the majority of practicing nephrologists were expatriate physicians, with local doctors representing only 14% of the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study's results showed adequate current nephrology trainee densities in high-income countries, many studies have shown decreased interest in the field. 14,27 Some high-income countries rely on foreign-trained doctors to cover shortages in nephrology manpower. For example, a study from Oman showed that the majority of practicing nephrologists were expatriate physicians, with local doctors representing only 14% of the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the trainees found the topic to be unappealing [ 2 ]. According to a survey from 5 medical schools in the United States: renal pathophysiology courses were too complex, lacked relevance or simply failed to stimulate interest [ 3 ]. Many students reported minimal nephrology exposure during their clinical rotations and even fewer were aware of the procedural work in nephrology, a feature than often attracts students to other specialties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have shown that some doctors are discouraged from a career in nephrology following experiences of the specialty at a junior level [ 25 , 26 ]. Examining the reasons behind this attrition should be a research priority for the specialty, as these trainees represent a missed opportunity for recruitment to the specialty.…”
mentioning
confidence: 99%